Measurements of plasma parameters in the divertor island of Wendelstein 7-X through line-ratio spectroscopy on helium. (4th September 2020) - Barbui, T.; Krychowiak, M.; Schmitz, O.; Bozhenkov, S.A.; Flom, E.; Fuchert, G.; Killer, C.; König, R.; Jakubowski, M.; Burgos, J.M. Muñoz; Pasch, E.; Scott, E.R.
Abstract: Electron temperature T e and density n e have been measured in the divertor island of Wendelstein 7-X by means of a new thermal He-beam system utilizing line-ratio spectroscopy. This system is equipped with a poloidal arrangement of five gas valves that allows to infer 2D plasma profiles T e ( R, Z ) and n e ( R, Z ) across the magnetic island forming the island divertor. A local maximum in T e ( R, Z ) was measured along the flux surfaces located between the island center and the outer separatrix. In the island center, characterized by closed field lines, a clear local minimum in T e was measured, indicating that no direct heat deposition occurs in this region and that the perpendicular heat flux from the core plasma into this domain is small. Increasing the island size leads to a reduction of the connection length in the scrape-off layer (SOL) and to a shift of the island center towards the divertor target. In this scenario, the T e ( R, Z ) are reduced in the entire island domain. Density profiles are found flat across the divertor island for both island size scenarios. These findings are supported by similar observations made with a reciprocating probe plunging through the same SOL island at the mid-plane of W7-X representing the upstream position in this 3D divertor geometry.